Association between Vitamin D Deficiency and Preeclampsia among Pregnant Females during First Trimester: Vitamin D Deficiency and Preeclampsia - Syed, Sadaf Zahra; Fatima, Bakhtawar; Waheed, Fatima; Akhter, Naheed; Butt, Sadiya (Pakistan Journal of Health Sciences, 2023)
One of issue during pregnancy among women is vitamin D insufficiency and studies have shown a dose–response relationship between development of preeclampsia and maternal vitamin D levels. Objective: To determine any association between vitamin D insufficiency in blood during the first trimester of pregnancy and development of preeclampsia. Methods: It was a Case Control study conducted in Department of Obstetrics and Gynecology, Lady Willingdon Hospital Lahore, from September 2019 to August, 2020. 150 women fulfilling selection criteria were enrolled from OPD of Lady Willingdon Hospital, Lahore. Informed consent was taken. Demographic variables e.g. age, gestational age, parity and BMI were recorded. Then females were divided in two groups i.e. cases with preeclampsia and controls without preeclampsia. Then medical record was obtained and vitamin D level during first trimester was noted. If vitamin D <20ng/dl, then vitamin D deficiency was labeled (as per operational definition). Data were entered and analyzed in SPSS version 20.0. Frequency and percentages were calculated for qualitative variables. Results: Mean age was 28.01±3.43 years. Mean gestational age was estimated as 32.84±4.75 weeks in cases and 32.24±3.55 in controls, Vitamin D deficiency in blood during the first trimester of pregnancy and development of preeclampsia shows that 90.67% in cases and 82.67% in controls had vitamin D deficiency with odds ratio of 2.03. Conclusions: We concluded that there is an association between vitamin D deficiency in blood during the first trimester of pregnancy and development of preeclampsia.